THU0384 The effect and safety of yisaipu (YISAIPU) in the treatment of patients with nonradiographic axial spondyloarthritis in china. (15th June 2017) - Zhao, M; Shi, G; Tao, Y; Wang, X; Cao, S; Lin, Z; Liao, Z; Kong, Q; Gu, J
Abstract : Background: Axial spondyloarthritis (axSpA) is a chronic inflammatory disease, which includes AS and nr-axSpA. Anti-TNF-α agents, such as Yisaipu (Yisaipu) are frequently used in nr-axSpA patients in China, but the related data is limited. Objectives: The aim of this research is to assess the efficacy and safety of Yisaipu in the treatment of patients with nr-axSpA in China. Methods: The inclusion of study population consisted of 150 patients who met the ASAS criteria for axial SpA but not the modified New York radiographic criteria for AS, had a score of ≥4 on the BASDAI or a score of ≥2.1 on the ASDAS-CRP and had been treated unsuccessfully with ≥1 NSAIDs for 4-week. Patients were assigned to receive Yisaipu (made in China) 50 mg/week and continued background NSAID treatment for 24 weeks (open-label study). At week 24, the primary efficacy end point was the improvement of ASDAS-CRP. Secondary end points included ASAS 20, ASAS 40, ASAS 5/6, ASAS partial remission and BASDAI. Safety was evaluated during scheduled visits. Results: 123 patients with active nr-axSpA were enrolled between April 19, 2014, and July 10, 2015. The mean age of the 123 nr-SpA patients was (25.3±5.9) years. The ASDAS-CRP and BASDAI decrease from 2.7±0.9 to 0.7±0.4, from 4.5±1.5 to 0.9±0.8, respectively between weeks 0 and 24. The patients achieved the ASDAS-CRP<2.1 was 96.7%. ASDAS-CRP major and important improvement were achieved by 41.4%, 79.8%, respectively at weeks 24. ASAS 20, ASAS 40, ASAS5/6 and ASAS partial remission were achieved by 75.0%, 54.8%, 64.5%, 89.3%, respectively at weeks 24. Yisaipu-treatment was associated with statistically significant improvements in all parameters, including BASFI, BASMI, PGA, PhGA, ESR and CRP concentrations. Most adverse events in the open-label phase were mild or moderate in severity. Conclusions: Yisaipu was effective and well-tolerated during the 24-week study period and was associated with a significant improvement in the signs and symptoms of active nr-axSpA. Disclosure of Interest: None declared